2020
DOI: 10.3904/kjim.2020.410
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of uric acid: hyperuricemia and hypouricemia

Abstract: The prevalence of chronic kidney disease (CKD) is increasing worldwide. Although hyperuricemia has been associated with CKD in many studies, it remains controversial whether this is the cause or the result of decreased renal function. Recent observational studies of healthy populations and patients with CKD have reported that uric acid (UA) has an independent role in the development or progression of CKD. Experimental studies have shown several potential mechanisms by which hyperuricemia may cause or promote C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 140 publications
(181 reference statements)
1
42
0
1
Order By: Relevance
“…It is well known that uric acid levels rise as kidney function decreases; however, there is controversy as to whether hyperuricemia directly worsens kidney function [ 71 , 72 ]. Although there is no consistent recommendation regarding the treatment of asymptomatic hyperuricemia in CKD patients, most Korean physicians treat asymptomatic hyperuricemia in CKD patients to prevent CKD progression and cerebrocardiovascular complications [ 73 ].…”
Section: Treatmentmentioning
confidence: 99%
“…It is well known that uric acid levels rise as kidney function decreases; however, there is controversy as to whether hyperuricemia directly worsens kidney function [ 71 , 72 ]. Although there is no consistent recommendation regarding the treatment of asymptomatic hyperuricemia in CKD patients, most Korean physicians treat asymptomatic hyperuricemia in CKD patients to prevent CKD progression and cerebrocardiovascular complications [ 73 ].…”
Section: Treatmentmentioning
confidence: 99%
“…This time, the pathogenesis is related to pro-inflammatory and pro-oxidative effects of UA. Other current pathogenesis incriminated in the onset and progression of already mentioned diseases are epithelial-to-mesenchymal transition in renal tubular cells, renal vasoconstriction mediated by endothelial dysfunction, and activation of renin-angiotensin system (RAAS) [ 12 ]. Some studies reported that high levels of uric acid may exert protective effects in neurological disorders, such as Parkinson’s disease [ 13 ], multiple sclerosis [ 14 , 15 ], Alzheimer’s disease [ 16 ], and vascular-disease-related dementia [ 2 ] through its extracellular anti-oxidative role.…”
Section: Introductionmentioning
confidence: 99%
“…It may be more appropriate to manage the SUA level in PD patients at a higher value within the normal accepted range. Because UA is the most abundant antioxidant in plasma, further research is needed to assess the safety of lowering serum UA to specific thresholds to produce safe guidelines [ 33 ], for men and women, and in patients with and without CVD or CKD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%